Fasting and surgery timing (FaST) audit. Issue 3 (March 2021) - El-Sharkawy, Ahmed M.; Daliya, Prita; Lewis-Lloyd, Christopher; Adiamah, Alfred; Malcolm, Francesca L.; Boyd-Carson, Hannah; Couch, Daniel; Herrod, Philip J.J.; Hossain, Tanvir; Couch, Jennifer; Sarmah, Panchali B.; Sian, Tanvir S.; et al.
Summary: Background & aims: International guidance advocates the avoidance of prolonged preoperative fasting due to its negative impact on perioperative hydration. This study aimed to assess the adherence to these guidelines for fasting in patients undergoing elective and emergency surgery in the East Midlands region of the UK. Methods: This prospective audit was performed over a two-month period at five National Health Service (NHS) Trusts across the East Midlands region of the UK. Demographic data, admission and operative details, and length of preoperative fasting were collected on adult patients listed for emergency and elective surgery. Results: Of the 343 surgical patients included within the study, 50% (n = 172) were male, 78% (n = 266) had elective surgery and 22% (n = 77) underwent emergency surgery. Overall median fasting times (Q1, Q3) were 16.1 (13.0, 19.4) hours for food and 5.8 (3.5, 10.7) hours for clear fluids. Prolonged fasting >12 h was documented in 73% (n = 250) for food, and 21% (n = 71) for clear fluids. Median fasting times from clear fluids and food were longer in the those undergoing emergency surgery when compared with those undergoing elective surgery: 13.0 (6.4, 22.6) vs . 4.9 (3.3, 7.8) hours, and 22.0 (14.0, 37.4) vs . 15.6 (12.9, 17.8) hours respectively, p < 0.0001. Conclusions: Despite international consensus on the duration of preoperative fasting, patients continue to fast from clear fluids and food for prolonged lengths of time. Patients admitted for emergency surgery were more likely to fast for longer than those having elective surgery.